2013
DOI: 10.1155/2013/275172
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mast Cells in Drug-Induced Gingival Overgrowth

Abstract: Mast cells (MCs) are multifunctional effector cells that were originally thought to be involved in allergic disorders. Now it is known that they contain an array of mediators with a multitude of effects on many other cells. MCs have become a recent concern in drug-induced gingival overgrowth (DIGO), an unwanted outcome of systemic medication. Most of the studies have confirmed the significant presence of inflammation as a prerequisite for the overgrowth to occur. The inflammatory changes within the gingival ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 66 publications
(68 reference statements)
0
15
0
1
Order By: Relevance
“…Recently, Subramani et al .,[22] observed that mast cells participate in many inflammatory oral diseases, particularly those associated with fibrosis. They possess very diverse roles ranging from proinflammatory to immunomodulatory.…”
Section: Role Of Matrix Metalloproteinasementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Subramani et al .,[22] observed that mast cells participate in many inflammatory oral diseases, particularly those associated with fibrosis. They possess very diverse roles ranging from proinflammatory to immunomodulatory.…”
Section: Role Of Matrix Metalloproteinasementioning
confidence: 99%
“…Cyclosporin can modulate local expression of renin angiotensin system components such as angiotensinogen, angiotensin II and its receptors in gingival tissues, and gingival fibroblast cells. [2223]…”
Section: Role Of Matrix Metalloproteinasementioning
confidence: 99%
“…The dose of the medicine, its usage period, serum concentrations, age of the patient, oral hygiene, level of inflammation at gums and genetic tendency have impact on gingival enlargement. Usually enlargement stops in toothless areas and after the medication is stopped [37,38].…”
Section: The Impact Of Polypharmacy On Oral and Dental Healthmentioning
confidence: 99%
“…An in vitro study using hamster cells treated with phenytoin and cyclosporine showed that cyclosporine increased signaling by TLR2 and TLR4, while phenytoin decreased this signaling with a decreased expression of adhesion molecules such as CD54 (47). The reduction in cell signaling induced by drugs such as phenytoin may alter the inflammatory response in gingival tissues, favoring bacterial invasion and proliferation and, therefore, may be an important factor in the pathogenesis of gingival fibrosis (48). Furthermore, cyclosporine-induced gingival overgrowth patients had a significantly higher number of TLR-4 expressing cells in the basal cell layer of the epithelium, as well as in connective tissue compared to healthy subjects (42).…”
Section: Tlrs and Drug-induced Gingival Overgrowthmentioning
confidence: 99%